The Effect of Workload, Work Discipline, and Competence on the Performance of Police Officers at the Banyuwangi Regional Police through Job Satisfaction as an Intervening Variable - Suwandono; Budi Santoso; Haris Hermawan (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2026)
This study aims to analyze the effect of workload, work discipline, and competence on the performance of police officers at Polresta Banyuwangi, with job satisfaction as an intervening variable. This research uses a quantitative approach with a survey method involving 219 respondents selected using proportional random sampling.Data were analyzed using Structural Equation Modeling (SEM) with WarpPLS. The results show that work discipline and competence have a positive and significant effect on job satisfaction and performance, while workload does not significantly affect job satisfaction or performance. Job satisfaction is proven to mediate the effect of discipline and competence on performance, but it does not mediate the effect of workload on performance.This study concludes that improving police officers’ performance is more influenced by competence and work discipline than workload.